2019
DOI: 10.3390/su11102947
|View full text |Cite
|
Sign up to set email alerts
|

Which Corporate Social Responsibility Performance Affects the Cost of Equity? Evidence from Korea

Abstract: This study analyzes the effect of corporate social responsibility activities on the cost of equity in Korea. We find that firms with better corporate social responsibility (CSR) performance generally exhibit cheaper equity financing. Considering three dimensions of CSR separately, we find that a higher “socially responsible management” significantly reduces the cost of equity by 1.13%-1.37% per annum and “Corporate governance” activity also marginally affects the cost of equity, while “environmental management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 53 publications
(81 reference statements)
1
14
0
2
Order By: Relevance
“…Studies that consider green investment have been conducted by Chariri et al (2019Chariri et al ( ), (2018, and Cheema et al (2017); Zhu et al, (2016); Eyraud et al (2013), Murovec et al (2012), Saxena andKhandelwal (2012), andEl Ghoul et al (2011). Meanwhile, studies on CSR aspects have only been conducted by Asogwa et al (2020), Eyasu et al (2020), and Nguyen et al (2020); Cupertino et al (2019); Ok and Kim (2019), Viviani et al (2019), Jain and Winner (2016), and Wahba and Elsayed (2015), and Khojastehpour and Johns (2014); Lanis and Richardson (2012); Uadiale and Fagbemi (2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that consider green investment have been conducted by Chariri et al (2019Chariri et al ( ), (2018, and Cheema et al (2017); Zhu et al, (2016); Eyraud et al (2013), Murovec et al (2012), Saxena andKhandelwal (2012), andEl Ghoul et al (2011). Meanwhile, studies on CSR aspects have only been conducted by Asogwa et al (2020), Eyasu et al (2020), and Nguyen et al (2020); Cupertino et al (2019); Ok and Kim (2019), Viviani et al (2019), Jain and Winner (2016), and Wahba and Elsayed (2015), and Khojastehpour and Johns (2014); Lanis and Richardson (2012); Uadiale and Fagbemi (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cupertino et al, (2019) believed that a focus on environmental, social and governance standards may enhance a company's long-term growth with a positive effect on its long-term value. Furthermore, Ok and Kim (2019) implied that enhancing socially responsible management can increase company value. Viviani et al (2019) concluded that good socially responsible (SR) level reduces the downside risk level of stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…They used a sample consisting 7380 firm years gathered from 22 developed countries and found that the firm-level corporate governance factors and characters impact the cost of equity capital primarily in the Common Law countries, which reflect high levels of financial development. Ok and Kim (2019) analyzed the effect of corporate social responsibility performance on the cost of equity in Korea. It was found that corporate governance affected the cost of equity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By reducing adverse behavior by customers and competitors, CSR helps highly leveraged firms keep customers and guard against rivals' predation. Ok and Kim (2019) [60] found that firms with better corporate social responsibility (CSR) performance generally exhibit cheaper equity financing. Cupertino et al (2019) [61] found that the environmental and social firm performance positively impacted corporate capital accumulation using a sample of US manufacturing firms from 2002 to 2017.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%